The Pacman Song Meaning Interpreted through Semiotics Analysis - Nuryanti, Dewi; Pragita, Salca (Talenta Publisher, 2023)
This study aimed to interpret the meaning of the song lyrics â€œPacmanâ€ by EAJ. It used the semiotic analysis by Michael Riffaterre. The research was qualitative descriptive research. Data for the research was the lyrics of the Pacman song by EAJ. The research found that the heuristic reading process in the â€œPacmanâ€ lyrics still discussed each lineâ€™s meaning. It was interpreted when a person loved someone and would give anything and did anything even if it ended painfully as long as he/she was together with his/her mate. Then â€œPacman and Loverâ€ was analyzed as a model. â€œCause my head says no, but my phone keeps calling you.â€ and â€œOver and Over, like itâ€™s Red Roverâ€ was analyzed as a variant. â€œPeople who love to die for someoneâ€ was analyzed as a matrix. Last, â€œone-sided loveâ€ was explored as a potential hypogram, and â€œPacmanâ€ was analyzed as an actual hypogram. This research concludes that the hidden meaning of â€œPacmanâ€ lyrics is when a person loves someone deeply. Even if a loved one hurts him, he will still love his lover.Â